THE ISSUES OF CRYPTOCURRENCY VALUATION - Nyam-Ochir, Damdindorj; Enkhee, Undarmaa; Lkhagvasuren, Khishigbayar (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
The fastest growing and most widespread payment and investment tool in the world is virtual assets, including cryptocurrencies. The concept of electronic money, Ecash, first emerged in 1983, and in 1989, the first electronic payment tool, DigiCash, began to be used for micropayments in the United States. Since then, the cryptocurrency Bitcoin has emerged, and in just over a decade, it has become a cryptocurrency with a market value of 1.8 trillion US dollars, accounting for more than 60% of the global cryptocurrency market. Therefore, we aimed to study how to assess the value of cryptocurrencies in this market, and currently, there are few provisions on valuation methods in the International Valuation Standards and other legal documents. According to our research and imagination, the researcher believes that it is appropriate to use different approaches to measure the value of the asset depending on its type.